From work with men and boys to changes of social norms and reduction of inequities in gender relations: a conceptual shift in prevention of violence against women and girls. Issue 9977 (18th April 2015) - Jewkes, Rachel; Flood, Michael; Lang, James
Summary: Violence perpetrated by and against men and boys is a major public health problem. Although individual men's use of violence differs, engagement of all men and boys in action to prevent violence against women and girls is essential. We discuss why this engagement approach is theoretically important and how prevention interventions have developed from treating men simply as perpetrators of violence against women and girls or as allies of women in its prevention, to approaches that seek to transform the relations, social norms, and systems that sustain gender inequality and violence. We review evidence of intervention effectiveness in the reduction of violence or its risk factors, features commonly seen in more effective interventions, and how strong evidence-based interventions can be developed with more robust use of theory. Future interventions should emphasise work with both men and boys and women and girls to change social norms on gender relations, and need to appropriately accommodate the differences between men and women in the design of programmes.